Parkinsonism and occupational exposure to pesticides. Issue 9 (1st September 2001) - Engel, L S; Checkoway, H; Keifer, M C; Seixas, N S; Longstreth, W T; Scott, K C; Hudnell, K; Anger, W K; Camicioli, R
Abstract : OBJECTIVE: To examine the risk of parkinsonism related to lifetime occupational exposure to pesticides among a cohort of men, mostly orchardists, in Washington State. METHODS: All 310 subjects in this study had previously participated in a cohort study of men occupationally exposed to pesticides. Subjects were given a structured neurological examination and completed a self administered questionnaire which elicited detailed information on pesticide (insecticide, herbicide, and fungicide) use throughout their working careers. Demographic characteristics were also sought. Subjects had a mean age of 69.6 years (range 49–96, SD 8.1). There were 238 (76.8%) subjects who reported some occupational exposure to pesticides, whereas 72 (23.2%) reported none. Parkinsonism was defined by the presence of two or more of rest tremor, rigidity, bradykinesia, and impairment of postural reflexes in subjects not on antiparkinsonian medication, or the presence of at least one sign if they were on such medication. Parkinson's disease was not studied explicitly because of the difficulty in distinguishing it from other parkinsonian syndromes. A generalised linear model was used to estimate prevalence ratios (PRs) for parkinsonism relative to history of farming, pesticide use, and use of well water. RESULTS: A PR of 2.0 (95% confidence interval (95% CI) 1.0 to 4.2) was found for subjects in the highest tertile of years of exposure to pesticides; a similarly increased, non-significant, PR was found for the middle tertile (1.9 (95% CI 0.9 to 4.0)), although a trend test did not show a significant exposure-response relation. No increased risks were found associated with specific pesticides or pesticide classes, nor with a history of farming or use of well water. CONCLUSION: Parkinsonism may be associated with long term occupational exposure to pesticides, although no associations with specific pesticides could be detected. This finding is consistent with most of the publications on this topic.